Synergy between BI, OJK and LPS in Constructing Economic Resilience in Indonesia Latest Discourse - rohman, M.Miftakhurrohman; Uswatun Nurul Husna; Afiyatul fadilah; Rinda Asytuti (Sahmiyya: Jurnal Ekonomi dan Bisnis, 2024)
The global financial crisis of 2008 exposed flaws in financial institutions around the world, including Indonesia's, which saw increased unemployment, market volatility, and economic downturn. In response, the government of Indonesia established the Deposit Insurance Corporation (LPS), the Financial Services Authority (OJK), and Bank Indonesia (BI) in order to preserve financial stability. To assist Indonesia's economic rehabilitation, these three organizations must work together on information sharing, policy coordination, and infrastructure development. This study employs a qualitative, descriptive methodology, namely a library research study. The Deposit Insurance Corporation (LPS), Bank Indonesia (BI), and Financial Services Authority (OJK) are all essential to preserving Indonesia's financial stability. LPS protects bank deposits, OJK supervises the financial services industry, and BI controls monetary policy the payment system. Resilience of the financial system depends on these institutions working together through infrastructure development, policy coordination, and information sharing. Indonesia (BI) is in charge of the payment system, monetary policy, and stability of the Rupiah. The Financial Services Authority (OJK) safeguards customers, fosters innovation, and keeps an eye on the financial industry. The Deposit Insurance Corporation (LPS) helps banks in distress and insures bank deposits. Coordination of policies and combined supervision by BI, OJK, and LPS is crucial to the stability of Indonesia's financial system.